End user satisfaction with Central Sterile Supply Department of a Tertiary care Teaching hospital - Malhotra, Monica; Kumar, Sunil (Innovative Journal of Medical and Health Sciences, 2021)
Hospital acquired infection or “nosocomial infection” adversely affects both patients and hospitals. Impact of nosocomial infections ranges from increased length of hospital stay, emotional stress, disability, death of the patients as well as increased hospital cost for the patients and providers. Studies in India have reported nosocomial infection rates from 8% to 58 %. The ultimate outcome of the services rendered in a hospital is judged by the level to which it satisfies its user .In our study 100 personnel working in various department of the hospital directly linked with the patient care were randomly selected and studied. The category of staff studied included doctors, nurses and others staff. In the study It was found that on an average 70 % staff was satisfied with the services provided by Central Sterile Supplies Department of SKIMS.